Understanding attitudes to immigration: The migration and minority module of the first European Social Survey - David Card; Christian Dustmann; Ian Preston (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2005)
Immigration control is an issue that figures prominently in public policy discussions and election campaigns throughout Europe. Although immigration may have positive effects on economic efficiency and growth in the receiving economy, it is often the negative aspects -or perceived negative aspects - of immigration that attract the most attention. In this paper, we use the immigration module of the European Social Survey (ESS), which we developed in collaboration with the ESS survey team, to investigate public opinions about immigration, and the various dimensions of economic, public and private life that individuals feel are affected by immigration. We show that there is substantial variation in the strength of anti)immigrant opinion across European countries, and that attitudes toward immigration also vary systematically with characteristics such as age, education, and urban/rural location. We propose possible interpretations of some of these regularities.
Keywords: 330; Migration; Survey; Attitudes